Diagnostic dilemma in post-abortion intrauterine retention: endometrial polyps mimicking retained products of conception - Wu, Wei-Fang; Yan, Shi-Han; Xu, Hai-Hua; Liu, Chao-Bin; Xie, Xi; Lin, Shun-He (Frontiers in Global Women's Health, 2025)
ObjectiveThis retrospective study investigated the characteristics of endometrial polyps identified during incomplete abortion management and evaluated differences between these polyps and retained products of conception.MethodsPatients with intrauterine retention within 4 months after abortion were enrolled in this study between January 2019 and December 2024. Twenty-six patients with pathologically confirmed endometrial polyps were included in the case group, while fifty-two patients with confirmed retained products of conception (RPOC) comprised the control group. The groups were matched in a 1:2 ratio based on gestational age (±1 week).ResultsTwenty-six study group patients were included; 69.2% (18/26) were nulliparous. Abortions occurred in gestational age of 6–14 weeks. No polyps were identified prior to subsequent surgical intervention. Hysteroscopy was performed on 24 women. In hysteroscopic cases, no endometrial polyp was larger than 2 centimeters in size. Compared with control group, the study group had lower gravidity (1 [0–3] vs. 2 [0–8], p = 0.025) and lower serum β-hCG levels (3.67 [0–799.1] mIU/ml vs. 21.08 [0–901.2] mIU/ml, p = 0.004). Ultrasonography indicated a lower rate of abundant blood flow (7.7% vs. 46.2%, p = 0.001) and smaller intrauterine volume (1.93 ± 2.55 cm3 vs. 5.42 ± 4.94 cm3, p = 0.001) in the study group. Additionally, the study group had a significantly longer interval from pregnancy termination to subsequent surgical intervention (51.5 ± 31.7 days vs. 38.2 ± 14.9 days, p < 0.001).ConclusionsEndometrial polyps should be considered in stable women after abortion with intrauterine retention present with low blood flow on doppler, low β-hCG levels, and prolonged retention, especially in women with lower gravidity. Hysteroscopy is recommended for accurate diagnosis and proper management, preventing unnecessary treatment for presumed retained products of conception.